Marital Conflict Resolution through Babadan Tenan in Banceuy Traditional Village, Subang Regency - Natasya Ekaputri Sadina; Ikrar Valentina Putri; Indra Indra; Fitriani Fitriani (Labor Jurusan Sosiologi Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This study examines the management of marital disputes in the indigenous community of Kampung Adat Banceuy, Subang Regency, which can affect social relations between families if not properly managed. Unlike previous studies that positioned Babadan Tenan within the normative perspective of customary law and Islamic law, this study aims to analyze the function of Babadan Tenan as a mediation and conflict resolution mechanism for marital disputes using Lewis A. Coser's functional conflict theory, particularly the concepts of the safety valve and the positive functions of conflict. The study employs a qualitative approach with a case study method through in-depth interviews, observation, and document analysis. The findings show that marital disputes are generally triggered by household economic problems, differing views between spouses, and arranged marriages. Babadan Tenan involves a three-stage resolution mechanism, namely pre-implementation, implementation, and post-implementation, carried out informally and flexibly by the customary leader as mediator. Tensions are channeled through Babadan Tenan, which functions as a safety valve to prevent conflicts from escalating further. Conflicts managed through Babadan Tenan also generate positive functions, as resolutions are directed toward solutions acceptable to both parties, including amicable separation. Agreements are grounded in the moral recognition of the customary community and help maintain social relations between families. This study affirms that customary mechanisms remain relevant as an alternative for resolving family conflicts based on local wisdom amid the modernization of law.